Influence of different anions on the surface composition of ionic liquids studied using ARXPS - Kolbeck, Claudia; Cremer, Till; Lovelock, Kevin; Paape, Natalia; Schulz, Peter; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans-Peter (Journal of Physical Chemistry B, 2009)
Angle-resolved X-ray photoelectron spectroscopy has been used to study the influence of different types of anions on the surface composition of ionic liquids (ILs). We have investigated nine ILs with the same cation, 1-octyl-3-methylimidazolium [CCIm], but very different anions. In all cases, an enrichment of the cation alkyl chains is found at the expense of the polar cation head groups and the anions in the first molecular layer. This enhancement effect decreases with increasing size of the anion, which means it is most pronounced for the smallest anions and least pronounced for the largest anions. A simple model is proposed to explain the experimental observations. © 2009 American Chemical Society.